A Lactobacilli diet that confers MRSA resistance causes amino acid depletion and increased antioxidant levels in the C. elegans host - Møller, Katrine Vogt; Nguyen, Hien Thi Thu; Mørch, Maria Grymer Metz; Hesselager, Marianne Overgaard; Mulder, Frans A. A.; Fuursted, Kurt; Olsen, Anders (Frontiers in Microbiology, 2022)
Probiotic bacteria are increasingly popular as dietary supplements but they also have potential as alternatives to traditional antibiotics. We have recently shown that pretreatment with the Lactobacillus spp. Lb21 increases lifespan of C. elegans and results in resistance towards pathogenic methicillin-resistant Staphylococcus aureus (MRSA). The Lb21-mediated MRSA resistance is dependent on the DBL-1 ligand of the TGF-β signaling pathway. However, the underlying changes at the metabolite level are not understood which limits the application of probiotic bacteria as timely alternatives to traditional antibiotics. In this study we have performed untargeted nuclear magnetic resonance based metabolic profiling. We report the metabolomes of Lactobacillus spp. Lb21 and control E. coli OP50 bacteria as well as the nematode-host metabolomes after feeding with these. We identify 48 metabolites in the bacteria samples and 51 metabolites in the nematode samples and 63 across all samples. Compared to the control diet the Lactobacilli pretreatment significantly alters the metabolic profile of the worms. Through sparse Partial Least Squares discriminant analysis we identify the 20 most important metabolites distinguishing probiotics from the regular OP50 food. Among the changed metabolites we find lower levels of essential amino acids as well as increased levels of the antioxidants ascorbate and glutathione. Since the probiotic diet offers significant protection against MRSA these metabolites could provide novel ways of combatting MRSA infections.